Несанкціоноване втручання в роботу електронно-обчислювальних машин, їх систем чи комп'ютерних мереж - Гаряєва, Ганна Михайлівна; Шевердін, Дмитро Олександрович (НТУ "ХПІ", 2013)
The article features the results obtained in the study, results and conclusions that can be used to further study the nature and characteristics of crimes in the use of computers (PCs), their systems and computer networks in the law-making activities in the preparation of amendments and additions to existing criminal Law of Ukraine in the learning process in teaching the course of the Special Part of Criminal Law, the relevant study course and in the preparation of scientific and practical manuals and guidelines.
Keywords: право кримінальне; злочини інформаційні; Кримінальний кодекс України